Determination of Investment Needs to Pursue Growth Targets through Incremental Capital Output Ratio (ICOR) - Suparmono Suparmono (Telaah Bisnis, 2021)
This article aims to analyze the effectiveness of investment as measured by the need for investment to produce output at a certain level, which in turn can determine the regional economic growth target. The analytical tool used is the incremental capital output ratio (ICOR) and the determination of economic growth targets. The ICOR value used in this study was calculated using three calculation approaches, namely Lag0, Lag1, and Lag2 data. The data used in this study is data from the economy of the Special Region of Yogyakarta until 2019. The result is that during the research period, there is a correlation between ICOR and economic growth, meaning that the lower the ICOR value, the value of economic growth will also increase. This shows that the effectiveness and efficiency of investment will result in a positive impact on economic growth.